Use of Risk Management Register Using Qualitative Risk Analysis Method for Land Drilling Works in Rokan Work Area - Rio PRAMANA; Reikman D. P. ARITONANG (PT Keberlanjutan Strategis Indonesia, 2025)
With the huge energy needs, especially oil, the Indonesian government is trying to manage it through the state-owned company Pertamina. Based on BP Migas data in 2022, Indonesia produced 31.4 million tons of oil, compared to the need, which was 2.2 times higher, namely 69.7 million tons. After the change of the new operator, which PMA previously managed to PHR WK Rokan, the government, represented by SKK Migas instructed to immediately carry out drilling activities so that national oil needs could be met. With the massive drilling activities carried out by PHR, where from 2021 to early 2024, drilling of more than 1000 new wells has been carried out. The purpose of this study is to map the risks of drilling activities that will be carried out in the future using the risk grouping method (Risk Register) in order to obtain an analysis of the dangers that will later be used to manage or control the possibility (probability) and impact (severity) of drilling activities that will be carried out next. The stages of work in onshore drilling are obtained from the existing drilling program, where all risks of the drilling stages to be carried out are grouped, given initial and additional barriers, so that a risk analysis is obtained in the form of initial mitigation.